Assessing the effect of learning with eye-fixation complexity analysis - Che Azemin, Mohd Zulfaezal; Ahmad Bazli, Aliya Fareeha; Taib, Ibrahim Adham; Mohd Tamrin, Mohd Izzuddin (Malaysia Technical Scientist Association, 2019)
The ability of an optometrist to extract relevant information from clinical printout will greatly affect their diagnosis. In this paper, an eye tracking methodology has been proposed as a non-intrusive mechanism to study the effect of learning among optometrist to-be in reading clinical data printout. A total of 10 clinical students were enrolled in this study. The PUPIL headset eye tracker and its software were used to record the image of eye fixation for each student before and after the exposure of OCULUS Twinfield printout educational slide presentation. These eye-fixation images were quantified with box-counting Fractal Dimension (FD) to study the eye fixation patterns. Using paired t-test / Wilcoxon signed-ranked test, the results showed that time taken, number of fixation and the complexity of the eye fixation has significantly reduced with p-value < 0.05 after the learning had been introduced. Exposure to the education slide had improved the ability of these students to target specific information and reduce the depth of information processing.